APLIKASI MEDIA PEMBELAJARAN ALAT MUSIK TRADISIONAL KHAS SUMATERA UTARA BERBASIS AUGMENTED REALITY - Haeqal, Rama Adys; Nasution, M Irwan Padli; Fakhriza, M (UIN Sumatera Utara Medan, 2023)
Augmented Reality (AR), is a technology with the idea of fusing the real world's dimensions with the virtual world's dimensions that are shown in real time. A three-dimensional object in augmented reality is depicted on a markerless surface using a distinctive pattern that the application can identify. Among the many applications for augmented reality is as a form of educational media. The lack of information conveyed on traditional North Sumatran musical instruments is one of the obstacles for students in recognizing traditional North Sumatran musical instruments. In this final project, an Augmented Reality application was developed for learning media for traditional North Sumatran musical instruments by displaying 2-dimensional objects into 3- dimensional objects in a more attractive way, thereby creating a sense of love for the culture and history of musical instruments in North Sumatra. participate in maintaining and preserving traditional North Sumatran musical instruments which have begun to be forgotten with the emergence of modern musical instruments. This application will be able to read markerless traditional musical instruments which will display three-dimensional musical instruments, sounds, and their history. This application is also equipped with materials and quizzes that serve to evaluate the user's understanding of the material.